OBJECT AND SUBJECT OF INFORMATION POLICY AS PUBLIC ADMINISTRATION DIRECTIONS - Anton Viktorovich Aristov; Nataliya Leonidovna Podvoyskaya (Современная наука и инновации, 2022)
The issues of the state information policy are considered as an activity aimed at the development of technical and technological means of production, distribution and storage of information, as well as at harmonizing the information space of the Russian Federation.